Measuring light-induced fungal ethylene production enables non-destructive diagnosis of disease occurrence in harvested fruits. (25th April 2020) - Guo, Han; Liu, Anran; Wang, Yunrui; Wang, Tan; Zhang, Wei; Zhu, Pinkuan; Xu, Ling
Highlights: Ethylene production by fungal pathogens of fruit crops is enhanced by light. The fungal ethylene production can be detected during host invasion. Light induction and real-time ethylene analysis facilitate disease diagnosis in harvested fruits. Abstract: Pathogenic fungi cause enormous losses to fruits, and ethylene (ET) is associated with disease development in fruit crops. In this study, ET production of several fungal pathogens was enhanced by light, probably through the free radicals produced by photochemical reactions. Real-time gas analysis showed a sharp increase in ET production when fungal cultures were moved from dark-to-light (DTL). Similarly, light accelerated ET production in the Botrytis cinerea -infected Arabidopsis thaliana plants even when pyrazinamide, the inhibitor for plant ET synthesis, was applied, suggesting that the fungus is responsible for ET production during host invasion. Furthermore, a sharp increase in ET production after DTL transition was observed in B. cinerea -infected tomatoes and grapes, but not in healthy or physically wounded fruits. Taken together, these findings indicate that the DTL-induced ET is specific to the plant materials with fungal infection, and thus represents a candidate marker for non-destructive disease diagnosis of harvested fruits.